Wearable Photoplethysmographic Sensor System with PSoC Microcontroller - Sonoda, Koji; Kishida, Yuji; Tanaka, Tomoya; Kanda, Kensuke; Fujita, Takayuki; Maenaka, Kazusuke; Higuchi, Kohei (2012 Fifth International Conference on Emerging Trends in Engineering and Technology, 2012)
This paper presents a wearable PPG (photoplethysmographic) sensor system with a PSoC micro controller unit (Cypress Semiconductor Corp., USA). We have developed a pulse wave monitoring system on earlobe, which has a PIC micro controller and analog circuits. However, analog sensors need some discrete parts, resulting in difficulty in reducing the system size. The PSoC micro controller includes a CPU, analog and digital blocks to configure mixed-signal circuits, and an internal oscillator in a single IC package. Therefore, PSoC allows designers to reduce the number of external discrete devices and the system size. The novel system consists of a photo interrupter, the PSoC, and the Bluetooth module, which are on PCBs (Printed Circuit Board) of 18, 13, and 10 mm in diameter, respectively. The photo interrupter detects the pulse wave due to the change in volume of blood vessels. The PSoC includes an analog filter, amplifiers, and digital circuits to calculate HR (heart rate) from the pulse wave of human body. The system was able to detect the pulse wave and transmit the HR data to a PC wirelessly. The power supply voltage is 3.3 V, and the total current consumption is about 51 mA. In comparison with the previous work, the area of discrete RCL (resistor, capacitor, and inductor) devices is reduced from 1230 mm2 to 466 mm2, and the number of such devices is reduced from 26 to 6.